INTERAKSI SOSIAL WARGA BELAJAR PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) INSAN CENDEKIA KELURAHAN SIALANG MUNGGU KECAMATAN TAMPAN KOTA PEKANBARU - Reza Fahrefi; Titi Maemunaty; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is descriptive with a quantitative approach which aimsto describe the results of the study with numbers. The weight of each answer is for VeryOften (SS) with a score of 4, Often (S) with a score of 3, Sometimes (KK) with a score of2, Never (TP) with a score of 1. The sampling technique uses simple random samplingtechnique (simple random sampling). The data collection technique in this study was aquestionnaire technique, which amounted to 65 statement items. Data obtained fromrespondents, amounting to 20 people for the trial sample and 38 people for the researchsample, with a critical level of 5%. After the questionnaire was tested, it turned out thatall items were valid, so that the entire instrument was declared reliable with AlphaCronbach = 0.995. From the research findings of the four indicators, it can beconcluded that the four indicators are classified as good. This is evidenced by thepresentation of the recapitulation of Social Interaction of learning citizens in package Cat the Center for Community Learning Activities (PKBM) of the Scholar of SialangMunggu Village, Tampan District, Pekanbaru City as a whole; (1) Cooperation (SS +S) of (23% + 51%) or 74%, (2) Accommodation or Adjustment (SS + S) of (22% +48%) or 70%, (3) Competition (SS + S) at (15% + 42%) or 57%, and (4) (TP) at (34%)or 34%, because Citizens Learning Package C did not take action against, threateningand coercing in them interact socially.Key Words: Social Interaction, Learning Citizens, PKBM Insan Cendekia